1983
DOI: 10.1111/j.1600-0722.1983.tb00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zendium toothpaste on recurrent aphthous stomatitis

Abstract: – A Double‐blind clinical trial with cross‐over was conducted for a period of 12 months in 25 patients with recurrent aphthous stomatitis (RAS). The effect of the amyloglucosidase and glucoseoxidase containing Zendium toothpaste on the discomfort, number of exacerbations, duration of exacerbation, number of ulcers and number of days with pain caused by RAS was studied. The use of Zendium significantly reduced the sensation of discomfort from RAS as compared to the use of placebo toothpaste (0.025>p>0.01). How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The present study used a larger panel of patients and a double-blind crossover trial to investigate the role of SLS dentifrice in ROU. This trial design is particularly appropriate as previous trials have shown a high placebo effect in ROU patients (Donatsky et al, 1983). Subjects completed a 2-week wash-out period before both the test and control phases during which they used the same paste as in the subsequent phase.…”
Section: Discussionmentioning
confidence: 99%
“…The present study used a larger panel of patients and a double-blind crossover trial to investigate the role of SLS dentifrice in ROU. This trial design is particularly appropriate as previous trials have shown a high placebo effect in ROU patients (Donatsky et al, 1983). Subjects completed a 2-week wash-out period before both the test and control phases during which they used the same paste as in the subsequent phase.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that elimination of the detergent sodium lauryl sulfate (SLS) from dentifrices can reduce or prevent RAS (130,131), but this has not been confirmed (132). Dentifrices containing amyloglucosidase and glucose oxidase that enhance the salivary peroxidase system are ineffective at reducing RAS (133–135), but a mouth rinse based on this produced ulcer resolution in 55% of patients (136).…”
Section: Topical Agentsmentioning
confidence: 99%
“…SLS is a strong denaturating substance and has the potential to denaturate the enzymes (12) included in the toothpaste tested by these authors; its addition was therefore probably avoided for this reason. The results observed by Hoogendoorn & Scholtes (ll), Koch (6), and Donatsky et al (5) may in fact be explained in terms of the lack of SLS rather than the presence of enzymes. It may be suggested that the denaturating effect of SLS on the oral mucosal layer induces an increased incidence of M U .…”
Section: %mentioning
confidence: 84%
“…In the latter case a significant decrease in the frequency of RAU was reported (6) when the patients brushed with the toothpaste containing the enzymes amyloglucosidase and glucose oxidase. In 1983 Donatsky et al (5) recommended use of toothpaste with the same composition for patients with RAU, even though their study did not demonstrate any convincing reducing effect on RAU after comparing the enzyme toothpaste with a placebo paste without the enzymes. The enzyme-containing toothpaste did not contain sodium lauryl sulfate (SLS), which is present in almost all other types of toothpastes (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation